2008
DOI: 10.1016/j.neuroscience.2008.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Underweight rats have enhanced dopamine release and blunted acetylcholine response in the nucleus accumbens while bingeing on sucrose

Abstract: The present study tested whether rats release more accumbens dopamine (DA) during a sugar binge when they are underweight vs. normal weight. Since acetylcholine (ACh) in the nucleus accumbens (NAc) normally increases as a meal progresses and satiety ensues, we also tested whether ACh release is altered when an animal has lost weight. Rats were maintained on daily 8-h access to chow, with 10% sucrose solution available for the first 2 h. Microdialysis performed on day 21, at normal body weight, revealed an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 40 publications
6
97
0
Order By: Relevance
“…It is unclear whether those alterations are premorbid or develop during the course of illness. The prospective studies in rodents that were exposed to over-or under-consumption of food (Avena et al, 2008;Carr, 2007;Johnson and Kenny, 2010) suggest adaptive dopamine-related changes to food intake, and it is possible that such adaptations also occur in AN and OB. Yet, premorbid traits may predispose to such changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear whether those alterations are premorbid or develop during the course of illness. The prospective studies in rodents that were exposed to over-or under-consumption of food (Avena et al, 2008;Carr, 2007;Johnson and Kenny, 2010) suggest adaptive dopamine-related changes to food intake, and it is possible that such adaptations also occur in AN and OB. Yet, premorbid traits may predispose to such changes.…”
Section: Discussionmentioning
confidence: 99%
“…Food restriction and weight loss have been associated with heightened brain dopamine-related reward response in rodents (Avena et al, 2008;Carr et al, 2003;Carr, 2007). Over-consumption of food on the contrary showed addiction-like dopamine D2 receptor downregulation in rodents in brain reward regions (Johnson and Kenny, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although early studies suggested that ACh might primarily suppress intake via satiety or aversion, since ACh levels rise gradually during food intake and after exposure to aversive tastes (Avena et al, 2008;Mark et al, 1992;Mark et al, 1995), more recent studies have implicated endogenous ACh in NAc and striatum in the appetitive motivation for food rewards (Perry et al, 2009;Perry et al, 2014;Pratt et al, 2007). For example, blockade of endogenous ACh in NAc by microinjections of the muscarinic antagonist scopolamine suppresses food intake, and establishes learned taste or place avoidances.…”
Section: Introductionmentioning
confidence: 99%
“…7 Animal studies reveal that the consumption of high-sugar or high-fat meals promotes the DA release in NAc. 7,12 The intake of a tasty meal for humans induces the DA release in a magnitude proportional to the meal degree of pleasure.…”
mentioning
confidence: 99%